Competitiveness assessment for real estate enterprises in china: A model‐procedure - Zhang, Xiaoling; Shen, Liyin; Wu, Yuzhe; C. N. Fan, Linda (International Journal of Strategic Property Management, 2009)
China’s accession to the World Trade Organization (WTO) in 2001 has allowed both domestic and overseas real estate enterprises to compete under the same market conditions. This has led to a more rigorous competition in the Chinese real estate market. Understanding this challenge is essential as it enables real estate enterprises to assess their competitiveness properly, and therefore adapt to their competition environment by applying adequate methods to improve their competitiveness. This paper presents an understanding on the applicability of various established competitiveness assessment methods. The characteristics of real estate firms are also presented with the appreciation of the Chinese environment. The study investigates the applicability of various established competitiveness assessment methods for real estate organizations in China considering the characteristics of real estate industry and the comments of the interviewees. The understanding on this applicability leads to the development of a model‐procedure for assessing the competitiveness of real estate firms. The model‐procedure employs various assessment methods in different stages in the process of examining the competitiveness of real estate businesses. The effectiveness of the application of the model‐procedure is evidenced through discussions with senior professionals. Then a case study is presented to illustrate how the model‐procedure can be applied. The findings of the study provide valuable references to study competitiveness assessment in other country’s real estate industries. First Publish Online: 18 Oct 2010